Preparation, biocontrol activity and growth promotion of biofertilizer containing Streptomyces aureoverticillatus HN6 - Wang, Tianhao; Ahmad, Shakil; Yang, Lin; Yan, Xiangnan; Zhang, Yunfei; Zhang, Shujing; Wang, Lanying; Luo, Yanping (Frontiers in Plant Science, 2022)
Nowadays, due to the excessive dependence on chemical fertilizers and pesticides in agricultural production, many problems, such as soil hardening and soil-borne diseases, have become increasingly prominent, which seriously restrict the sustainable development of agriculture. The application of microbial fertilizer prepared by biocontrol microorganisms can not only improve soil structure and increase fertility but also have the function of controlling diseases. Streptomyces aureoverticillatus HN6 has obvious disease prevention and growth promotive effect, which can improve the rhizosphere fertility of plants and even regulate the rhizosphere microbial community of plants. Based on the comparison of frame composting and natural composting, we used the response surface method to optimize the preparation conditions of Streptomyces HN6 bacterial fertilizer. The results showed that natural composting not only produced higher composting temperatures and maintained long high temperature periods in accordance with local conditions, but was also more suitable for composting in the field according to local conditions. Therefore, the substrate’s conductivity changed more, the ash accumulation increased, and the substrate decomposed more thoroughly. Thus, this composting method is highly recommended. Additionally, Streptomyces HN6 microbial fertilizer EC20 can reduce cowpea fusarium wilt and promote cowpea growth. The number of plant leaves, plant height and fresh weight, increased significantly in the microbial fertilizer EC20. Moreover, Streptomyces HN6 fertilizer EC20 could significantly induce soil invertase, urease and catalase activities. Our study highlights the potential use of Streptomyces HN6 as a biofertilizer to improve plant productivity and biological control of plant pathogenic fungi.